What you really need to lead - Kaplan, Robert Steven (Harvard Business Review Press, 2015)
You might believe that leaders are born, not made. Perhaps you think that you need to hold an important job to be a leader―that you need permission to lead. Leadership is one of the most important aspects of our society. Yet there is enormous disagreement and confusion about what leadership means and whether it can really be learned